2022
DOI: 10.1097/sla.0000000000005639
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Outcomes After Adrenalectomy for Primary Aldosteronism – Early is Accurate

Abstract: Objective: We aimed to investigate the postoperative trend in blood pressure (BP)-related outcomes [BP and antihypertensive (AHT) drug use] during the year following adrenalectomy for primary aldosteronism (PA) to determine the optimal timing for outcome assessment and to determine the necessary follow-up length. Background: Since the course of BP-related outcomes after adrenalectomy is unknown, the optimal timing of outcome assessment and follow-up duration are not clear. Methods: In this retrospective si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(50 reference statements)
0
1
1
Order By: Relevance
“…Interestingly, for patients with 2 follow-up visits (usually early postsurgical evaluation and 1-year follow-up), there was a change in clinical status for one-fifth of patients. This is contradictory with recent results 21 questioning the need for routine follow-up in referral centers. In the study from Suurd et al, defined daily doses of antihypertensive drugs were found to be stable from 1 month to 1 year postoperatively.…”
Section: Discussioncontrasting
confidence: 85%
“…Interestingly, for patients with 2 follow-up visits (usually early postsurgical evaluation and 1-year follow-up), there was a change in clinical status for one-fifth of patients. This is contradictory with recent results 21 questioning the need for routine follow-up in referral centers. In the study from Suurd et al, defined daily doses of antihypertensive drugs were found to be stable from 1 month to 1 year postoperatively.…”
Section: Discussioncontrasting
confidence: 85%
“…6 We show herein that clinical outcomes do not significantly change from short-to long-term follow-up assessment, in agreement with a recent report. 42 In contrast, biochemical outcomes were progressively impaired, with incomplete biochemical success increasing >3× in the long term and the recurrence of aldosteronism occurring in around 1 in every 4 individuals with prior short-term biochemical remission. This is markedly higher than the just under 4% recurrence previously reported, 43 but this disparity is potentially accounted for by differences in the time intervals of outcome assessments and the use of diverse criteria for biochemical outcome assessment.…”
Section: Discussionmentioning
confidence: 99%